Unofficial Nominations of Modern Political Discourse in the Media: Intercultural Aspect - Shulska, Nataliia; Kostusiak, Nataliia; Zubach, Oksana; Pakholok, Vasil; Bukina, Nataliia; Kevliuk, Iryna; Hammoor, Marta (My University, 2023)
The article analyzes unofficial nominations in contemporary Ukrainian and foreign (American, German, French, etc.) political discourse. It is noted that unofficial proprietary units in political communication are characterized by such features as individuality, expressiveness, evaluability, and informativeness. It was determined that the so-called “second” names of political figures have an impact on the effectiveness of communication with citizens, the creation of one's own image and individual style of communication. The unofficial anthroponyms of this group of bearers show original features at the motivational, lexical-semantic, word-forming, and pragmatic levels. The motivational factor and the nature of the creation of nicknames revealed in unofficial communication and public rhetoric of country leaders and political figures, broadcast through the media, were investigated. The impact of nicknames on the formation of the image of a person and a place in the political process is traced. Unofficial names are characterized in detail according to the seven most common motivational groups: 1) nicknames from one's own official surnames and names; 2) nominations indicating the external features of the bearer; 3) naming according to the internal features of denotations (character, habit, behavior, preferences); 4) nicknames motivated by an incident or event in the politician's life; 5) unofficial anthroponyms based on similarity to other famous people or characters; 6) nominations indicating occupation or activity; 7) nicknames that appeared as a result of political activities of the nominees. It was found that most often unofficial names of politicians are given when they hold the highest government positions, because attention to them is special at this time. Surnames are not always given only in view of the characteristic that belongs to the named person. It happens that an unconventional proper name “sticks” to an official because of rumors rather than official facts. It has been studied that, according to the connotative color, nicknames are less often funny and ironic, usually they are offensive and sarcastic, express invective semantics. The pragmatic basis for the emergence of unofficial names is usually extralingual information related to the personal characteristics of the nominee, his lifestyle, tactics of communicative behavior, achievements or defeats in the political sphere. It is noted that the unofficial anthroponymic system of modern political discourse accumulates information about linguistic, humorous, and ethno-cultural specifics. Considering the fact that multilingual nicknames are involved in the analysis, the research is based on an intercultural aspect.
Keywords: informal communication; political discourse; nickname; media; civil servants; public rhetoric; political anecdote